Synthesis and Characterization of Rod-Bent Shape Compounds Containing Bis-Oxadiazole - M. Rasol, Aqeel; R. Jber, Nasreen (Al-Nahrain Journal of Science, 2023)
In this work, two new mesomorphic bent-rod shape compounds containing bis-oxadiazole rings are described. The relationship between the compound structure and the mesomorphic behavior as 3,3’-benzene-1,4-diylbis [5-(4-nitrophenyl)-1,2, 4-oxadiazole] and 3,3’-benzene-1,4-diylbis [5-(4-chlorophenyl)-1,2,4-oxadiazole] were established using different terminal groups (i.e., NO2, Cl). The mesomorphism was categorized using POM and DSC, while the compounds structure were characterized using FT-IR and 1HNMR.